Teores de nitrogênio, fósforo e potássio em pontos de deposição de urina bovina em solos de textura argilosa e arenosa - Lima, Rosangela Correa de (2021)
Bovine urine contains a large amount of nutrients in its composition and, therefore, can be an important route for nutrient cycling in integrated agricultural production systems. In this context, the work was developed in two different experimental protocols. The first was carried out in an oxisol, with the objective of evaluating the effect of nitrogen fertilization and grazing pressure in ryegrass pasture on the behavior of nutrients in bovine urine deposition sites in the city of Abelardo Luz - SC. The experimental design was randomized blocks, in a factorial scheme, with three replications. The first factor was the time of application of nitrogen (N) in the system: N applied on pasture (N-Fert. Pasture) and these were the only plots to receive nitrogen topdressing at a dose of 200 kg of N ha-1 in Single dose. These were compared with plots called N-Fert Grains, which did not receive nitrogen fertilization in the grazing stage, and received it in the previous season. The second factor was pasture height, high height (AA) and low height (BA), 25 and 10 cm, respectively. To evaluate the behavior of nutrients in the soil (N, P and K) from bovine urine, collections were carried out on different days (0 (zero), that is, immediately after urination, on the third (3rd), sixth (6th) and twelfth (12th) day after urination), at equidistant distances from the central point of urination 0 cm (midpoint of the wet area), 25, 50 and 75 cm from the central point of urination, and at different depths to the along the soil profile, 0-5; 5-10; 10-20 and 20-40 cm. The second experiment aimed to evaluate the behavior of nutrients at bovine urination points in a mixed pasture of Lolium multiflorum + Avena strigosa as a function of nitrogen application and the presence of trees in integrated agricultural production systems, in a soil with a sandy texture, in Ponta Grossa – PR. The experimental design was randomized blocks, in a factorial scheme, with three replications. Two nitrogen fertilization treatments (90 and 180 kg N ha-1, in the form of urea, with a single application during the pasture phase) were alternated with two integrated systems: only Crop-Livestock (ILP) and Crop-Livestock-Forest ( ILPF). The evaluations were carried out in the same way as the first experiment. Nitrogen fertilization performed on the pasture causes an increase in the concentration of nitrogen (13.8 g L-1) and potassium (26.2 g L-1) excreted via urine. Pasture areas managed with higher grazing pressure (low height 10cm), have lower N and P contents, and higher potassium content in the soil at urine urination points. Higher levels of nitrogen, phosphorus and potassium were observed in the urine points in the wooded system, since in these systems the nutrient uptake by forage plants was reduced due to their shading, leading to a reduction in pasture dry matter production . Still, for phosphorus, the lowest dose of nitrogen caused a higher concentration of phosphorus in the soil, due to lower extraction by plants due to the lower availability of nitrogen. The highest levels of nitrogen and potassium in the soil are observed at the point where urine urination occurred (central point), and the area of, action/diffusion of urinary N does not exceed 25 cm from the central point of urination, and the action of potassium remains at the central point, with no lateral diffusion up to 25 cm. Due to the low contribution of phosphorus in animal urine, there is no change in the levels in the soil, not even in the central point. Ammonium is converted to nitrate up to the sixth day after urination, potassium and phosphorus present high values soon after urination and seems to be influenced by environmental factors (precipitation), in their availability over time. The highest concentrations of ammonium, nitrate, phosphorus and potassium were observed in the superficial layers of the soil (0-10 cm). And although, in this study, nitrate, ammonium and potassium leaching was not observed in the sampled urine points, in none of the studied soils, up to a depth of 40 cm, it is warned that the adoption of more intensified production systems (with the inclusion of animals in pasture and increased nitrogen fertilization) should be conducted under conditions that provide high extraction of nutrients from the soil by plants, aiming to reduce the risk of losses.